Awareness and utilization of social security and other government schemes by elderly population of Budge-Budge II block of West Bengal - Mausumi Basu; Aparajita Mondal; Kuntala Ray; Soma Chakrabarti; Abhipsa Dey (Indian Association of Preventive and Social Medicine, 2024)
Introduction: : Geriatric population are most vulnerable population, they suffer from various physical illness, mental issues, inancial crisis etc. WHO report showed that the world's population of people aged 60 years and older will be doubled by 2050 (2.1 billion). According to census 2011report, India has 10.1% elderly population and West Bengal has 11.3%. The purpose of the study is to assess the level of awareness on social security& other government schemes, its utilization and to explore the barrier of utilization. Method: An explanatory sequential mixed methods observational study, cross-sectional in design was conductedin Budge-Budge II block of West Bengal among 150elderly population (≥ 60 years) selected by 30 cluster random sampling from March-May 2023 using a pre-designed, pre-tested, structured schedule by face-toface interview. Quantitative data was analysed by SPSS v25.0, and binary logistic regression was performed. Qualitative data was analyzed thematically with IDI guide. Results: Out of 150 elderly, mean age group of the study population was 67.5±4.24 years, 53% were male, and 87% of the study population had awareness on old age pension scheme. However, 83% showed bad utilization. Socioeconomic status [AOR 5.27 (1.98- 13.97)],current employment status [AOR 6.48 (1.12-37.30)] economic dependency [AOR 7.59 (1.71-33.79)] had statistically signiicant higher odds of adequate awareness in the multivariable model. Current employment status, economic dependency showed signiicant association with good utilization and socio demographic characteristics. Conclusion: Majority of the study population were between 65 to 70 years and were aware of old age pension scheme. Old age pension scheme was maximally utilized schemes.